Pelatihan Keterampilan Berkomunikasi Bahasa Inggris Bagi Pramusaji Kedai di Kawasan Wisata Aik Berik - Dira Permana; Siti Syafi’atul Qomariyah; Muhammad Arief Rizka (Jurnal Pengabdian UNDIKMA, 2020)
The English communication skill training for shop waiters in the tourism area of Aik Berik aims to provide theoretical and practical knowledge about the use of a variety of tourism English, expressions and vocabulary commonly used in providing services especially to foreign tourists. This training activity involved the shop waiters around the tourism area of Aik Berik. The mentors of this training were lectures and students majoring in English who had proficient English skills. The training activity took a place around the shop location in the tourism area of Aik Berik, Central Lombok. The training method included material presentation including greetings, showing the way, kinds of food and beverage, menus, price lists, fruits, expressions, mini conversations and the practice of making short conversations among participants regarding the materials that had been taught. The results of the evaluation during the training showed high interest and enthusiasm of the shop waiters in participating in the whole series of training activities ranging from socialization to the implementation of the training. The shop waiters also showed an increase in the capability of using the language, expressions and vocabularies as well as better self-confidence in providing services for tourists. Participants also gave high appreciation to the presence of lectures and students as trainers and hoped that similar activities could continue to be carried out in order to enrich insight and improve communication skills and confidence of tourism activists, especially shop waiters in the Aik Berik tourism area.